Impact Of Antenatal Corticosteroids On Neonatal Hypoglycemia And Hyperbilirubinemia In Preterms - A Prospective Cohort Study - Pravallika Deepthi, Sathi Sri Naga Sai; P, Vimarshitha.; V R, Sudha Reddy (Journal of Neonatal Surgery, 2025)
Background: Antenatal corticosteroids (ACS) are routinely administered to pregnant women at risk of preterm delivery to promote fetal lung maturation and reduce neonatal morbidity and mortality. However, emerging evidence suggests that ACS may influence neonatal outcomes such as hypoglycemia and hyperbilirubinemia, with inconsistent findings across studies. Objectives: To evaluate the association of antenatal corticosteroid exposure with neonatal hypoglycemia and hyperbilirubinemia in preterm neonates. Methods: This prospective cohort study was conducted over 1.5 years at R.L. Jalappa Hospital. A total of 120 preterm neonates (<37 weeks gestation) were enrolled—60 with maternal ACS exposure and 60 without. Neonates with maternal diabetes, sepsis, hypoxic ischemic encephalopathy, or Rh incompatibility were excluded. Blood glucose was monitored every 6 hours for 72 hours post-birth. Hyperbilirubinemia was assessed via transcutaneous or serum bilirubin every 12 hours. Data were analysed using SPSS v21.0, with p < 0.05 considered statistically significant. Results: Hypoglycemia was significantly more common in the ACS group (55%) compared to the non-ACS group (5%) (p < 0.001), with an odds ratio of 23.22 (95% CI: 6.53–82.48). In contrast, the rate of hyperbilirubinemia was comparable between groups (41.7% in ACS vs. 53.3% in non-ACS, p = 0.20). Conclusion: Antenatal corticosteroid exposure in preterm neonates is significantly associated with an increased risk of neonatal hypoglycemia but not hyperbilirubinemia. These findings highlight the importance of vigilant glucose monitoring in ACS-exposed preterm infants, particularly during the first 72 hours of life.